2015
DOI: 10.1080/17457300.2015.1061563
|View full text |Cite
|
Sign up to set email alerts
|

First motorcycle-exclusive lane (Motovia) in Colombia: perceptions of users in Cali, 2012–2013

Abstract: This study's goal was to evaluate the pilot exclusive lane for motorcycles (Motovía) in Cali, Colombia, from the perception of its users in 2012-2013. A cross-sectional study using roadside surveys plus a qualitative component of individual semi-structured interviews was carried out. Road users' perceptions were investigated before and after implementation of lane dividers (LD) and were compared with other roads in the city. Perceptions were compared using chi-square tests. In the study, 293 motorcyclists, 111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…However, there was also a reduction in the proportion of RTI over time (Figure 1), which differs from a study in Sao Paulo, Brazil, which found an increase in the frequency of RTIs over time [25]. The different TSCI trends in these two cities may re ect the socioeconomic differences between them, and a less complicated transportation system in Cali with successful implementation of road safety interventions [26,27].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, there was also a reduction in the proportion of RTI over time (Figure 1), which differs from a study in Sao Paulo, Brazil, which found an increase in the frequency of RTIs over time [25]. The different TSCI trends in these two cities may re ect the socioeconomic differences between them, and a less complicated transportation system in Cali with successful implementation of road safety interventions [26,27].…”
Section: Discussionmentioning
confidence: 63%
“…Comparing AIS grade at admission vs. last follow-up we found that the correlation between both variables was 96.52% (p<0.0001). AIS grades B and C were the classi cations with higher changes in AIS grade from admission to last follow-up, with 57.58% (19) and 71.05% (27) of the individuals classi ed that way in admission remaining the same at the last follow-up, respectively. When individuals were admitted with an AIS grade B injury, they had at their last visit either AIS grade A or D in 15.15% (5) both, and when individuals were admitted with an AIS grade C, 28.95% (11) were AIS grade D at their last follow-up (See Figure 2).…”
Section: Ais At Last Follow-upmentioning
confidence: 98%
“…Exclusive motorcycle lanes have reduced conflicts at intersections and have increasingly reduced the number of accidents. In Columbia [14], the transportation authority implemented an exclusive motorcycle lane, named Motovia (or Motomia), to separate these vehicles and optimize the traffic loads. In a follow-up survey, the transportation authority asked users to evaluate Motovia; 88% of respondents noted a decreased in travel time, and 87% of them responded that motorcycle-only lanes made commuting easier.…”
Section: Exclusive Motorcycle Lanesmentioning
confidence: 99%
“…Another LMIC study on exclusive motorcycle lanes found this was highly accepted by motorcyclists as it facilitated riding and reduced commute time, in addition to promoting safety on the road [99].…”
Section: Engineeringmentioning
confidence: 99%